Troubled Projects in Construction Due To Scant Risk Management - B, Subramanyam; R, Iswarya (International Journal of Engineering and Technology, 2018)
This paper will focus on troubled projects in construction due to inadequate and insufficient risk management. Inadequate risk management has the ability to severely impact construction project. The main objective of the present paper is to attempt a composition of already known risk management process, at such way that it can be applied by the modern enterprises that deal with the undertaking or/and implementation of constructional work. This paper describes about the main sources for the failure of a construction project such as no initial risk assessment, inadequate documentation and tracking, irregular & incomplete status reporting, failure to define parameters etc. The methodology contains examining existing data, results and created a checklist for all those who are involved in construction project disasters. It can be applied at all stages in the project cycle, from the earliest assessments of strategy to initiation, planning, implementation and closure. Risk management will also provide advantages in better accountability and justification of decisions, by providing a well-suited and robust process that supports decision-making.Â
Keywords: Risk; Management; Assessment; Project Cycle; Decision Making.